An international survey of building energy codes and their implementation. (1st August 2017) - Evans, Meredydd; Roshchanka, Volha; Graham, Peter
Abstract: Buildings are key to low-carbon development everywhere, and many countries have introduced building energy codes to improve energy efficiency in buildings. Yet, building energy codes can only deliver results when the codes are implemented. For this reason, studies of building energy codes need to consider implementation of building energy codes in a consistent and comprehensive way. This research identifies elements and practices in implementing building energy codes, covering codes in 22 countries that account for 70% of global energy use in buildings. These elements and practices include: comprehensive coverage of buildings by type, age, size, and geographic location; an implementation framework that involves a certified agency to inspect construction at critical stages; and building materials that are independently tested, rated, and labeled. Training and supporting tools are another element of successful code implementation. Some countries have also introduced compliance evaluation studies, which suggested that tightening energy requirements would only be meaningful when also addressing gaps in implementation (Pitt&Sherry, 2014; U.S. DOE, 2016b). This article provides examples of practices that countries have adopted to assist with implementation of building energy codes. Highlights: Access to climate and other benefits of building energy codes depends on implementation. The study considers building energy code implementation in 22 countries. Elements and practices in implementing building energy codes are identified. Among elements are: code coverage, institutions, building checks, incentives, training.